2023
DOI: 10.1002/adbi.202200236
|View full text |Cite
|
Sign up to set email alerts
|

Genistein, a Soybean Isoflavone, Promotes Wound Healing by Enhancing Endothelial Progenitor Cell Mobilization in Rats with Hemorrhagic Shock

Abstract: Severe trauma and hemorrhaging are often accompanied by delayed cutaneous wound healing. Soybean isoflavone is a natural phytoestrogen that has attracted great attention due to its protective effects against various injuries. Endothelial progenitor cells (EPCs) are precursor cells with directional differentiation characteristics. This study is to determine whether genistein (GEN), an isoflavone in soybean products, benefits wound healing in hemorrhagic shock (HS) rats by promoting EPC homing and to investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Of particular interest has been the study of Mediterranean diets or diets rich in soy isoflavonoids/flavones [220][221][222][223] and their effects on CVD, dementia, and metabolic disease in post-menopausal females. One component of such diets is genistein, a soybean isoflavone [224], and a molecule that can exert its influence via ER-beta, as well as has effects on endothelial cells [225][226][227][228][229]. A clinical trial of genistein alone has been reported to have a beneficial effect on postmenopausal females with metabolic syndrome [230].…”
Section: Conclusion and The Way Forwardmentioning
confidence: 99%
“…Of particular interest has been the study of Mediterranean diets or diets rich in soy isoflavonoids/flavones [220][221][222][223] and their effects on CVD, dementia, and metabolic disease in post-menopausal females. One component of such diets is genistein, a soybean isoflavone [224], and a molecule that can exert its influence via ER-beta, as well as has effects on endothelial cells [225][226][227][228][229]. A clinical trial of genistein alone has been reported to have a beneficial effect on postmenopausal females with metabolic syndrome [230].…”
Section: Conclusion and The Way Forwardmentioning
confidence: 99%
“…[40,62] Hence, the findings infer that Col-KA-HA-LO biocomposite biomaterial is proangiogenic in nature which elicits the secretion of VEGF and expression of its receptor, VEGF-R2 to promote sprouting angiogenesis. [40,[63][64][65]…”
Section: Gene and Protein Level Expression Studiesmentioning
confidence: 99%
“…Genistein has a higher binding affinity for ERβ than ERα and its activity depends on endogenous estrogen levels and ER expression (Irrera et al, 2017;Čoma et al, 2021). It has the unique ability to selectively act as an agonist or antagonist in a dose-and tissue-specific manner and has been shown to improve skin repair while exerting antineoplastic and chemopreventive properties in both in vitro and in rodent models (Emmerson et al, 2010;Marini et al, 2010;Park et al, 2011;Pawlicka et al, 2022;Peng et al, 2023). Genistein was shown to modulate angiogenesis in human and mouse endothelial cells and induce macrophage polarization to a pro-repair phenotype, two important processes during physiological wound healing (Abron et al, 2018;Berndt et al, 2018;Peng et al, 2023).…”
Section: Selective Estrogen Receptor Modulatorsmentioning
confidence: 99%
“…It has the unique ability to selectively act as an agonist or antagonist in a dose-and tissue-specific manner and has been shown to improve skin repair while exerting antineoplastic and chemopreventive properties in both in vitro and in rodent models (Emmerson et al, 2010;Marini et al, 2010;Park et al, 2011;Pawlicka et al, 2022;Peng et al, 2023). Genistein was shown to modulate angiogenesis in human and mouse endothelial cells and induce macrophage polarization to a pro-repair phenotype, two important processes during physiological wound healing (Abron et al, 2018;Berndt et al, 2018;Peng et al, 2023). Accordingly, genistein reduced inflammation and oxidative stress in early-stage diabetic mice wounds and accelerated wound closure and improved tensile strength in ovariectomized mouse wounds (Emmerson et al, 2010;Marini et al, 2010;Eo et al, 2016).…”
Section: Selective Estrogen Receptor Modulatorsmentioning
confidence: 99%